Early Neolithic Settlement Patterns in Northern Dalmatia - Horvat Kristina (De Gruyter, 2021)
This article focuses on the early Neolithic settlement patterns in northern Dalmatia, located in the middle of the eastern Adriatic. At the present state of research, a total of 35 Neolithic sites have been known in this region, 26 of which belong to the Early Neolithic. Observing the type and character of the early Neolithic sites, their micro-topographic features, proximity and availability of resources, organization of life in relation to environment requirements, continuity of life at a particular location, and economic strategies, we come to the conclusion that the early Neolithic settlement patterns in northern Dalmatia were determined by natural landscape and its resources. They are the postulate and basis for the development of different aspects of social life and economy, as well as the starting point for the interpretation of the character and dynamics of the development of the early Neolithic communities in this area. The site locations, stratigraphic relations, and radiocarbon dating also suggest movements of the early Neolithic communities. The movements seem to have taken place exclusively within the fields. Discussion whether it was one or several simultaneous communities/settlements remains limited, since the state of research does not allow precise attribution of the site to certain chronological segments of the Early Neolithic.